تعليم القران برواية قالون عن نافع في مدينة بنغازي دراسة نقدية في المناهج - Essam A.A.Lali
Dealing with this study the subject of the ‘Education of the Koran Story Qaaloon Nafeh from study in the city of Benghazi in cash in the curricula’ where no longer a novel Qaaloon Nafeh from more stories prevalent in the city of Benghazi in particular, Libya, in general, and therefore this study is aimed to identify the reasons that led to the spread of a novel Qaaloon of Nafi, As well as to identify the method used in the education of the Holy Qur’an, in the city of Benghazi, and the most important books adopted in the education of the provisions and assets of the novel, and has been strengthening the study identifying. The study to achieve its objectives in the curriculum descriptive, historical, and the study of the results to, inter alia: The method followed in the memorization of the Holy Koran in the city of Benghazi has proved its success, despite the emergence of other ways of competing, which depend on information technology or conservation by reading the Holy Quran without reviews, as the study proved that the method used in education Aware on the quality of the conservation for approval to write, In spite of the entry of a number of contradicting views to the city of Benghazi in the present era, the people stick to novel Qaaloon Nafeh from their familiarity with the rest of the accounts or frequent Koranic readings.